Enhancing visible-light-activity of Ti-based MOFs based on extending the conjugated degree of organic ligands and photocatalytic degradation process and mechanism in real industrial textile wastewaters. Issue 6 (December 2021) - Guo, Ximing; Tian, Xueyao; Xu, Xin; He, Jinru
Abstract: In the manuscript, we developed a novel strategy to effectively improve the visible light absorption of Ti-based MOF by extending the conjugated degree of organic ligands in Ti-based MOFs. The freebased 5, 10, 15, 20-tetraphenylporphyrin (H2 TCPP) as organic linkers was used to facilely synthesize Ti-based MOFs (Ti-TiTCPP MOFs). The structural, morphologic and optical properties of Ti-TiTCPP MOFs were investigated. Ti-TiTCPP MOFs was applied to photocatalytic degradation of rhodamine B(RhB) and the photocatalytic degradation performances of Ti-TiTCPP MOFs were compared with that of NH2 -MIL-125(Ti) MOFs under mercury lamp, xenon lamp and daylight lamp irradiation, respectively. The results showed the photocatalytic degradation performances of Ti-TiTCPP MOFs are superior to that of NH2 -MIL-125(Ti) MOFs in visible region. Furthermore, the photocatalytic degradation mechanism of Ti-TiTCPP MOFs was investigated in detail based on the electrochemical and photoelectrochemical results associated with previously reported photocatalytic degradation mechanisms of NH2 -MIL-125(Ti). The possible electrochemical and photoelectrochemical reactions and the changes of Gibbs free energy were analyzed. The degradation possible pathways of RhB and the emerging main intermediate contaminants were carefully analyzed by HPLC-HRMS under the present different solution parameters. And then the photocatalytic system based on Ti-TiTCPP MOFs was successfully applied to deal with real industrial textile wastewaters. Graphical Abstract: Undoubtedly key issues in photocatalysis to be solved lies in the more efficient utilization of the solar spectrum. We developed a new strategy by extending the conjugation of aromatic rings of organic ligands with respect to the parent Ti-oxo clusters associated with the enhanced optical absorption. Using H2 TCPP instead of NH2 -BDC as organic ligand to synthesize titanium based MOFs, the corresponding energy gap from 2.46 eV of NH2 -MIL-125(Ti) reduced to 1.94 eV of Ti-(Ti-TCPP) MOFs, which will effectively improve the utilization efficiency of solar spectrum. We expect that the versatility of the strategy of extending the conjugation degree of organic ligands to realize the utilization of titanium-based materials in the visible light region presented here will allow the fabrication of various novel titanium-based materials based on various macrocyclic organic ligands with strong absorption in visible region, opening the way for their use in visible photocatalytic application. ga1 Highlights: We develop extending the conjugation of aromatic rings of organic ligands associated with the enhanced optical absorption. The energy gap from 2.46 eV of NH2 -MIL-125(Ti) reduced to 1.97 eV of Ti-(Ti-TCPP) MOFs. The photocatalytic degradation mechanism of Ti-(Ti-TCPP) MOFs was investigated. The degradation pathway of RhB and the emerging main intermediate contaminants were analyzed by HPLC-HRMS.